Chemical Oxidation Of Cyanide Species By Ozone With Irradiation From Ultraviolet Light ? Introduction - Charles E. Mauk (Society for Mining, Metallurgy & Exploration, 1975)
In 1970, recognizing the great need for an economical, high capacity chemical oxidation process for wastewater treatment, Houston Research began a fundamental study of the available technology, Included was waste characterization; oxidation chemistry for molecular oxygen, ozone and catalyst initiators; kinetics of reaction; gas-liquid contacting methods; and optimization of staged reactors for mixed wastes. Although ozone is the most powerful oxidizer available, the literature contains contradictory reports of its speed and effectiveness. It is now felt to be most likely that many of these early investigations were limited by the ineffectual transfer of ozone from the gas phase into the liquid, and so the investigators were really observing the effects of mass transfer and erroneously trying to interpret the results as if they were chemical reaction data. HR's work considered the cost and effectiveness of gas-liquid contacting in a packed tower, gas sparged contactor, ejector with hold-up tank, and a completely mixed, sparged contactor. The sparged, mixed contactor was found to be most effective and least expensive, and a later investigation settled on the reactor configuration shown in Figure 1 because of its effectiveness of mass transfer and because it lends itself to direct scale-up techniques using laboratory data to design larger reactors.